Prevalence of Risks for Eating Disorders among Undergraduate University Students: A Cross-sectional Study from United Arab Emirates - Heyam Dalky; Adam Khraisat; Mona Albalushi; Sara Ibrahim; Abrar Ahmed; Fatima Ali; Reem Ibrahim (Jordan University of Science and Technology, 2023)
Background: Eating disorders are psychological disturbances that result in severe and long-lasting abnormal eating patterns and consequences to a variety of physical and psychological components of health. Objectives: To determine the prevalence of risk to eating disorders among Emirati female undergraduate university students aged from 18 to 21 years at a higher college at UAE. Methods: Utilizing a Cross-sectional design, a total of 501 students recruited conveniently to participate in this study. A questionnaire consisted of demographical and eating pattern sections and the Eating Attitudes Test-26 (EAT-26) was used and shared with the students online. Results: The prevalence of female students with risks of eating disorders was 13.97%. The most frequent (13.6%) statement chosen by students was “I am terrified of being overweight.” Almost, 50% of the students were not satisfied with their weight, and 48.1% were dissatisfied with their physical appearance. Only 8.18% of the female students have a family history of EDs, and 8.98% were confirmed cases of eating disorders. Yet, the study revealed no statistically significant correlations between age, (r= 0.036, P= 0.416); BMI (r= 0.015, P= 0.734) or meals/day (r= -0.076, P= 0.087) and EAT-26 scores.   Conclusion: The risks of eating disorders in the current study were lower compared to previous studies. Regardless, education programs are required to increase awareness regarding eating disorders. Implications for Nursing: Extended community-based educational programs are suggested to enhance female students’ knowledge about EDs, there consequences on health, and methods to promote healthy eating habits and positive attitudes toward body image.